A conversation analysis of turn-taking strategies in the 2024 U.S. presidential debate - Zuhayr, Muhammad Rizqullah; Rahayu, Famala Eka Sanhadi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
This study investigates turn-taking strategies employed by Donald Trump and Joe Biden in the 2024 U.S. presidential debate. Using Conversation Analysis (CA) as the methodological framework, the research examines how interruptions, overlaps, pauses, and topic shifts are managed to negotiate control, assert dominance, or maintain authority in a high-stakes political context. Data were drawn from the official debate recording and analyzed qualitatively. The findings reveal that both verbal and nonverbal cues function as strategic tools in shaping debate dynamics and influencing audience perceptions of leadership and credibility. By situating turn-taking within the field of political communication, this study contributes to understanding the structural mechanisms underlying political discourse and shows how conversational strategies reflect power relations and persuasion beyond rhetoric and content.